Predictors of Five-Year Outcomes in Patients with Acute Coronary Syndromes - Luca Di Vito; Giancarla Scalone; Federico Di Giusto; Filippo Bruscoli; Simona Silenzi; Adelina Selimi; Arianna Massari; Domenico Delfino; Federico Guerra; Pierfrancesco Grossi (Journal of Cardiovascular Development and Disease)
Background: Residual risk after acute coronary syndromes (ACSs) continues to affect prognosis. We investigated the impact of female sex, non-ST-segment–elevation myocardial infarction (NSTEMI), diabetes mellitus (DM), and chronic kidney disease (CKD) on coronary atherosclerosis extent, culprit stenosis location, and bio-humoral data. The rate of both major adverse cardiovascular events (MACE) and non-fatal recurrent coronary events (RCE) was additionally evaluated. Methods: We enrolled 1404 ACS patients and followed them for up to 5 years. Coronary culprit and non-culprit stenoses were analyzed using angiography. Biohumoral data was assessed at admission and at 1 month and 12 months after discharge. Patients were compared based on sex, NSTEMI, DM, and CKD presence. Results: NSTEMI patients had a higher number of total coronary stenoses (3.5 vs. 3.3, p = 0.013) and non-culprit stenoses (2.3 vs. 1.6, p = 0.0001). Non-culprit percent stenosis was significantly greater in NSTEMI as compared to STEMI patients (57.9% vs. 47.1%, p = 0.0001). DM patients had a higher frequency of bifurcation lesions (41% vs. 25%, p = 0.0001). CKD patients showed a higher prevalence of left main disease (3.4% vs. 1.5%, p = 0.038). Female patients had higher LDL-cholesterol values at 1 month and 12 months. NSTEMI, DM, and creatinine level were independent predictors of MACE. NSTEMI patients had an increased risk of non-fatal RCE. Conclusions: NSTEMI, DM, and creatinine levels at admission were independent predictors of MACE in the first 5 years after an ACS.